(untitled) (Research, Society and Development, 2022)
In coffee farming, there is interest in reducing the incidence and costs in the management of weeds, with polyethylene mulching being a promising alternative, providing increased production and profitability of agricultural activity. In this context, this work was carried out with the objective of evaluating the effect of polyethylene mulching and fertilizer sources on chlorophyll levels, productivity and beverage quality. The experiment was installed at the Federal University of Uberlândia, Campus Monte Carmelo. The planting of the crop, cultivar IPR 100, was carried out in February 2019, using spacing of 3.5 m between rows and 0.7 m between plants and drip irrigation. The design used was in randomized blocks with four blocks in a 3 x 2 factorial scheme (mulching colors x fertilization types). The experiment consisted of six treatments: (1) white/black mulching with conventional fertilization; (2) white/black mulching with controlled release fertilization; (3) silver/black mulching with conventional fertilization; (4) silver/black mulching with controlled release fertilization; (5) absence of mulching and conventional fertilization and (6) absence of mulching and controlled release fertilization. In 2021, referring to the first crop of the crop, yield, percentage of unripe, cane green, cherry, raisin and dry fruits, sensory analysis and classification of grains in terms of size and shape were determined. Regarding the use of mulching, there was no increase in the productivity of processed coffee in relation to the control treatment, with an average of 47 bags per hectare. The use of mulching showed a decrease of 14% in the chlorophyll content compared to the control, however, mulching accelerates the maturation of the fruits with an increase of 17.33% of dried fruits. There was no significant difference in the sensory analysis of beverage quality, with an average of 81.5 points. The mulching showed a reduction of 19.74% for the big boring and an increase of 17.82% for the medium boring. Fertilizer sources and mulching do not have a significant effect on the phytotechnical parameters of irrigated coffee.